Pengendalian Organisme Pengganggu Tanaman Melalui Solarisasi Tanah: Pengendalian Organisme Pengganggu Tanaman Melalui Solarisasi Tanah - Kiki Kusyaeri Hamdani; Heru Susanto (Universitas Bangka Belitung, 2020)
Plant-disturbing organisms such as pests, pathogens, and weeds cause problems in crop cultivation so they need proper handling. Soil solarization is an alternative to pest control. This paper discusses information on the control of disruptive organisms by solarizing technology. Some of the components that play a role in the solarization process, namely the sun as an energy source, plastic mulch as an energy source converter, and soil moisture as a trap and conductor of heat produced by plastic in deeper soil depths. Solarization of the soil is environmentally friendly and is carried out before planting by managing heat energy from solar radiation. The best soil solarization is by using transparent plastic sheets because they are translucent, where most of the light is transmitted through the plastic sheet and only a little is absorbed and reflected. High soil temperatures due to soil solarization can suppress soil pathogens, soil pests, and weed propagules and can increase soil fertility, growth, and crop yield.